Catalogue of Javanese and Sasak Texts - Marrison, G.E., (Asian Studies - Book Archive pre-2000., 1999)
This catalogue contains descriptions of the romanized transliterations of manuscripts from Lombok in Javanese and Sasak kept by the Historical Documentation Department of the Koninklijk Instituut voor Taal-, Land- en Volkenkunde in Leiden (Or. 508). The 506 items in this collection were collected between 1932 and 1941 by the Gedong Kirtya, Singaraja, Bali.